2017
DOI: 10.36510/learnland.v10i2.810
|View full text |Cite
|
Sign up to set email alerts
|

“Let’s Just Stop and Take a Breath”: A Community-Driven Approach to Mindfulness Practice in a High Poverty Elementary School

Abstract: This case study describes how a high-poverty, linguistically and culturally diverse elementary school came to embed mindfulness in its curriculum and what adults perceived to be the outcomes of the program on students’ well-being. This qualitative case study is based on 25 interviews with teachers, administrators, and community members; classroom observations; and relevant documents. Participants indicated that practicing mindfulness improved student well-being through greater self-awareness and increased abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Other studies have demonstrated similar effects of mindfulness practiced in classrooms (Meiklejohn et al, 2012;Harpin et al, 2016). The next theme, students having access to a wider range of strategies to cope with intense emotions as they arise, further helps teachers with classroom management and empowers students to build stronger awareness and regulation, with shared understanding and language surrounding emotions, the classroom and school environment becomes more of a harmonious container and cohesive community, as in results found by Haines et al (2017). Finally, this community provides concrete clues about the role of principal leadership and commitment to mindfulness practices schoolwide, also shown by Hudson et al (2020).…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have demonstrated similar effects of mindfulness practiced in classrooms (Meiklejohn et al, 2012;Harpin et al, 2016). The next theme, students having access to a wider range of strategies to cope with intense emotions as they arise, further helps teachers with classroom management and empowers students to build stronger awareness and regulation, with shared understanding and language surrounding emotions, the classroom and school environment becomes more of a harmonious container and cohesive community, as in results found by Haines et al (2017). Finally, this community provides concrete clues about the role of principal leadership and commitment to mindfulness practices schoolwide, also shown by Hudson et al (2020).…”
Section: Discussionmentioning
confidence: 96%
“…In a recent article (Haines et al, 2017), our seven-person research team describes the methodological elements of the full descriptive case study upon which this current writing is based. Briefly noted, the full case is a single, diverse urban K-5 elementary school in northern New England that was in its third year of integrating mindfulness practices across the school's formal and informal activities.…”
Section: Doing "Data" Differently and Sensitizing Ourselves To Sociommentioning
confidence: 99%
“…Having been asked by a member of a local nonprofit mindfulness organization to conduct a qualitative case study documenting mindfulness practices at a local school, I assembled a team of researchers interested in community-engaged research. Conducted as a service to the community as well as for the field of education, we aimed to provide a descriptive and accessible case report of how the mindfulness initiative came to be as well as its effects on the students, teachers and community (Haines et al, 2017).…”
Section: Entanglementsmentioning
confidence: 99%
“…The Cultivating Awareness and Resilience in Education (CARE) program promoted mindfulness and also resulted in an increase in adaptive emotional regulation, improved relationships, and a positive learning environment (Jennings et al, 2017). Mindfulness intervention not only helped trauma sensitive children but had positive effects for all children in the classroom as well as the classroom teacher (Haines, 2017;Jennings et al, 2017;van de Weijer-Bergsman, 2012).…”
Section: Mindfulness Interventionmentioning
confidence: 99%
“…Mindfulness practice in the classroom produced a shift in teachers' perceptions of trauma sensitive children and teaching overall (Haines et al, 2017). Teachers experienced less stress as they practiced self-care, were proactive instead of reactive, and developed a calm mindset to teach with compassion and empathy (Kavia & Murphy, 2021).…”
Section: Mindfulness Interventionmentioning
confidence: 99%